1984
DOI: 10.1161/01.cir.70.2.178
|View full text |Cite
|
Sign up to set email alerts
|

Ergonovine-induced myocardial ischemia: no role for serotonergic receptors?

Abstract: Because ergonovine appears to produce coronary contractions by a serotonergic (5-HT) mechanism, we attempted to prevent ergonovine-induced ischemia in patients with vasospastic angina by pretreatment with ketanserin, a new selective 5-HT blocker. We studied seven patients with consistently positive results of ergonovine testing (ST segment elevation in three and ST segment depression in four). Ergonovine testing was performed before and after a bolus of 10 mg of ketanserin (all patients) and infusion of 2 to 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1986
1986
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…The concentrations of both 5-HT and TxA2 released presumably from aggregating platelets, are elevated in the coronary sinus blood of patients with angina involving coronary artery disease and vasospasm (Robertson et al, 1981; Van den Berg et al, 1989). In this scenario it would be anticipated from our results that 5-HTI-like receptor-mediated contraction would be augmented and thus provide an explanation for the failure of 5-HT2 receptor antagonists such as ketanserin to relieve vasospastic angina (De Caterina et al, 1984;Freedman et al, 1984).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The concentrations of both 5-HT and TxA2 released presumably from aggregating platelets, are elevated in the coronary sinus blood of patients with angina involving coronary artery disease and vasospasm (Robertson et al, 1981; Van den Berg et al, 1989). In this scenario it would be anticipated from our results that 5-HTI-like receptor-mediated contraction would be augmented and thus provide an explanation for the failure of 5-HT2 receptor antagonists such as ketanserin to relieve vasospastic angina (De Caterina et al, 1984;Freedman et al, 1984).…”
Section: Discussionmentioning
confidence: 78%
“…Coronary vasospasm, occurring spontaneously or induced by ergonovine, is not prevented by the 5-HT2 receptor antagonist ketanserin; hence the role of 5-HT in vasospastic angina has been questioned (De Caterina et al, 1984;Freedman et al, 1984). However, it is now apparent that in some human blood vessels, including the umbilical, coronary, basilar and pial arteries, 5-HT can elicit contraction via ketanserin-resistant 5-HTI-like receptors in addition to ketanserin-sensitive 5-HT2 receptors (MacLennan et al, 1989;Connor et al, 1989;Parsons et al, 1989;Hamel & Bouchard, 1991).…”
mentioning
confidence: 99%
“…Available vasodilators administered systemically are not always sufficient for the complete control of severe variant angina 57,58 and appear to have a smaller dilator effect on pre-arteriolar vessels than on proximal coronary arteries. Complete cardiac denervation, 59 serotonin 60,61 and thromboxane A2 62 blockade did not abolish episodes of coronary spasm. Therefore, the time has come to try and identify novel specific therapeutic targets against the strong coronary constrictor stimuli and against key molecular components of the enhanced constrictor responsiveness that typically characterizes these large and small vasomotor disorders.…”
Section: Innovative Research Strategiesmentioning
confidence: 81%
“…In a similar study, however, McFadden et al (1991) included patients with Prinzmetal's angina (diagnosed previously by intracoronary challenge with ergometrine (ergonovine)) and found that intracoronary infusions of 5-HT caused spasm (zero flow) which was resistant to ketanserin (McFadden et al, 1992). Ketanserin does not prevent either ergometrineinduced ischaemia (Freedman et al, 1984) or spontaneous attacks of variant angina (De Caterina et al, 1984) in man and although ergometrine activates many different types of receptors including a-adrenoceptors , both it (Muller-Schweinitzer, 1980;Sakanashi & Yonemura, 1980;Brazenor & Angus, 1981;Holtz et al, 1982), and the antimigraine drug methysergide (Saxena, 1974;Brazenor & Angus, 1981), cause contractions via receptors other than a-adrenoceptors. Thus, in the dog isolated coronary artery, ergometrine was found to be a potent agonist at unspecified 5-HT receptors (Brazenor & Angus, 1981) whilst in the rabbit saphenous vein, ergometrine was demonstrated to be a potent 5-HT1-like receptor agonist (MacLennan & Martin, 1990).…”
Section: Introductionmentioning
confidence: 99%